Congenital disorders associated with platelet dysfunctions - Nurden, Paquita; Nurden, Alan T. (Thrombosis and Haemostasis, 2008)
Genetic defects of the megakaryocyte lineage give rise to bleeding syndromes of varying severity. Blood platelets are unable to fulfill their hemostatic function of preventing blood loss on vessel injury. Spontaneous bleeding is mostly mucocutaneous in nature. Most studied are deficiencies of glycoprotein (GP) mediators of adhesion (Bernard-Soulier syndrome) and aggregation (Glanzmann thrombasthenia) which concern the GPIb-IX-V complex and the integrin αIIbβ3, respectively. Defects of primary receptors for stimuli include the P2Y12 ADP receptor pathology. Agonist-specific deficiencies in the platelet aggregation response and abnormalities of signaling pathways are common and lead to trauma-related bleeding. Inherited defects of secretion from storage organelles, of ATP production, and of the generation of procoagulant activity are also encountered. In some disorders, such as the Chediak-Higashi, Hermansky-Pudlak, Wiskott-Aldrich and Scott syndromes, the molecular lesion extends to other cells. In familial thrombocytopenia (FT), platelets are produced in insufficient numbers to assure haemostasis. Some of these disorders affect platelet morphology and give rise to the so-called ‘giant platelet’ syndromes (MYH9-related diseases) with changes in megakaryocyte maturation within the bone marrow and premature release of platelets. Diseases of platelet production may extend to other cells and in some cases interfere with development. Transfusion of platelets remains the most common treatment of severe bleeding, management with desmopressin is common for mild disorders. Substitute therapies are available including rFVIIa and the potential use of TPO analogues for FT. Stem cell or bone marrow transplanation is being used for severe diseases while gene therapy may be on the horizon.
Keywords: Platelets; inherited disorders; platelet function; platelet production; treatment